Covid-19 Outbreak: The impact of citizen’s demographic attributes on satisfaction with the government during MCO 1.0 / Siti Hajjar Mohd Amin ... [et al.] - Mohd Amin, Siti Hajjar; Abdullah, Aida; Mohamed Ali, Abdul Jalil; Mohd Shafie, Siti Aishah; Mohd Wahid, Siti Daleela (2021)
All governments worldwide strive to achieve public satisfaction; nevertheless, this is a difficult task, as evidenced by the previous literature on citizen satisfaction, which including citizen expectations, experiences, past attitudes, and prior attitudes toward government. As a result, various administrative reform agendas have directly linked the need to reform public services to become more client-oriented to promote citizen satisfaction with public services to increase citizen satisfaction with public services (Van de Walle, 2018). The Malaysian government has implemented a comprehensive reform program throughout the last three decades, and it continues now. However, and in a contradictory manner, service delivery performance has continued to fall short of public expectations (Faiez & Rao, 2019). Failing public service delivery attracts the attention of the media, the scrutiny of political leaders, and the displeasure of the public (van den Bekerom et al., 2021). Fitch Solutions reported that the Covid-19 outbreak had increased political risks in Malaysia as more citizens become increasingly dissatisfied with the government's handling of the Covid-19, which will harm policymaking and policy continuity, as well as social stability, because of the pandemic (Mung, 2021, June 8). Previous researchers acknowledged that the level of citizen satisfaction was not thoroughly investigated throughout the crisis and that further research was required. As a result, the purpose of this paper is to investigate the relationship between citizen demographic characteristics and satisfaction during the first phase of the mobility control order during the Covid-19 epidemic.